ممارسة النشاط البدني والرياضي التربوي ودوره في التقليل من الخجل الاجتماعي لدى التلاميذ في مرحلة التعليم الثانوي. (دراسة ميدانية بثانويتي خامد عامر والعقيد شعباني محمد بولاية الأغواط) - gouasmia, aissa (sports creativity, 2025)
This research aims at exploring the role of practicing educational sporting and physical activity, by the pupils, in reducing social shyness of adolescents. Here, the researcher used the scale of social shyness where it was distributed to a random sample of pupils, practicing and non-practicing sports. The number of the pupils is 210, between male and female, from the different secondary schools of Laghouat. After the statistical study, following the SPSS statistical bundle, the results have revealed that practicing educational sporting and physical activity has an effective role in reducing social shyness.